Image denoising using fractional integral - Huang Guo; Xu Li; Chen Qing-li; Wang Ming-rong (2012 IEEE International Conference on Computer Science and Automation Engineering, 2012)
In order to preserve more image details information while image denoising, the fractional integral operator was introduced to signal processing. The method proposed in this work constructed the corresponding mask of image denoising by setting a smaller fractional order, and controlled the effect of image denoising by the way of iteration, so it achieved fine-tuning of image denoising. The experimental results show that the image denoising algorithm based on fractional integral proposed in this work compared with the traditional image denoising algorithm not only enhances the signal-to-noise ratio of image but also better retains the edge and texture details of image.